Celiac Disease and Cancer: Epidemiological Evidence, Diagnostic Challenges, and Future Research Directions - Ayoubi, Saman; Nazemalhosseini, Ehsan; Rezaei Tavirani, Mostafa; Jahani-Sherafat, Somayeh; Rostami-Nejad, Mohammad (Asian Pacific Journal of Cancer Biology, 2026)
Celiac disease (CD) is an autoimmune condition affecting multiple systems of the body. It is triggered in people with specific genetic profiles upon eating gluten. Current estimates suggest that about 0.5 to 1 percent of the global population is affected. Failure to follow a gluten-free diet (GFD) in these patients can cause side effects such as resistant CD. Various studies have reported that failure to follow a GFD increases the risk of diseases such as cancer. This review analyzed prevailing theories on epidemiological findings, diagnostic complexities, and avenues for further investigation. In the first part of the study, the relationship between CD and types of cancer was discussed, which showed that, based on previous studies, gastrointestinal cancers and intestinal lymphoma are most closely related to CD. Also, the frequency of ovarian cancer, breast cancer, and colon cancer in CD is significantly lower. In the next part of the study, the relationship between CD in children and types of cancer in this age group was analyzed based on studies. The results showed that intestinal lymphoma and thyroid cancer are the most common types of cancer in children. Also, in the next part of this study, the GFD’s effect on cancer types was examined. The studies reviewed in this section showed that in some cases, a GFD can reduce the risk of cancer. In another part of this study, cancer diagnosis methods in CD were minimally examined. The results showed that one of the critical challenges in celiac patients is the timely and accurate diagnosis of cancer in them, which can reduce mortality and even improve the treatment of these patients. However, these views need further investigation, and this review study cannot be sufficient to prove such a theory. To continue this study, descriptive or cohort research is recommended to investigate the association between CD and GFD and the prevalence of various cancers in these patients in a larger population.